(3eUMa TQjas ((3eMeO YGQa jGbhJ s)
(3ChdgG (B:s
(3ShQI GaGJMI GdMeO ddg QH GdYGdejf GdQMef GdQMje eGdc jhe GdOjf s
(3BNQgG (B:s
(3hYGafG ef cd HdGA GdOfjG hYPGH GdCNQI HMQeI GdbQBf HQMeJc jG CQMe GdQGMejf hUdi Gddg Ydj NjQ Ndbg eMeO YGQa s
(3BjGJ ef GdbQBf (B" (3GdaGJMI (B/ (3LRA ef GdHbQI (B/ (3GdYGdb (B/ (3GdbOQ GdHjfI (B/(3GdRdRdI (B/ (3GdYGOjGJ (B/ (3GdbGQYI (B/ (3GdJcGKQ (B/(3GdfGSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcJH GdSeGhjIs